Diagnostic dilemma: Radicular cyst or keratocystic odontogenic tumor? - Shubhankar Dasgupta; Shalu Rai; Deepankar Misra; Sapna Panjwani; Nivedita Singh (Wolters Kluwer Medknow Publications, 2015)
Keratocystic odontogenic tumor was previously considered as a common cyst of developmental origin but now it is considered as a tumor of the oral cavity with high recurrence rate and it has an ability to mimic other jaw cysts. Present study is a case report of a 19 year old male presenting with apainful swelling in right lower face region. On clinical and radiographic examination, a provisional diagnosis of Radicular cyst was given. Histopathological examination revealed Keratocystic Odontogenic Tumor. KOT may look similar to endodontic lesion. The lesion was successfully treated by complete enucleation. The aim of the study is to report and distinguish a case of keratocystic odontogenic tumor simulating Radicular cyst because of its aggressive behavior and high recurrence rate.